2023
DOI: 10.3390/nu15061445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Pandemic on Metabolic Status and Psychological Correlates of a Cohort of Italian NAFLD Outpatients

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a potentially progressive condition characterized by the presence of fat in more than 5% of hepatocytes, representing the hepatic expression of metabolic syndrome (MetS). A reduction of at least 5–7% in initial body weight improves the metabolic profile underlying NAFLD. The aim of our study was to evaluate the effects of the COVID-19 lockdown on a cohort of non-advanced NAFLD Italian outpatients. We identified 43 patients with 3 available time point visits in our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated that patients with non-alcoholic fatty liver disease experiencing psychological distress were less likely to adhere to a healthy lifestyle [ 50 ]. Specifically, they observed a trend of more prominent alterations in psychophysical health status, especially in the affective domains of anxiety, depression, and somatization, in patients who could not adopt lifestyle changes leading to weight loss [ 50 ]. This suggests that psychological vulnerabilities, such as depression, are associated with a negative impact on the ability of patients with MetS to make effective lifestyle changes and their HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that patients with non-alcoholic fatty liver disease experiencing psychological distress were less likely to adhere to a healthy lifestyle [ 50 ]. Specifically, they observed a trend of more prominent alterations in psychophysical health status, especially in the affective domains of anxiety, depression, and somatization, in patients who could not adopt lifestyle changes leading to weight loss [ 50 ]. This suggests that psychological vulnerabilities, such as depression, are associated with a negative impact on the ability of patients with MetS to make effective lifestyle changes and their HRQoL.…”
Section: Discussionmentioning
confidence: 99%